ROLE OF GUDADI MODAK IN THE MANAGEMENT OF AMLAPITTA W.S.R TO DIET AND LIFESTYLE - Thakur, Rinky; Sharma, Naresh; Nanda, *Gopal C (International Journal of Ayurveda and Pharma Research, 2017)
In present scenario with hasty and agonizing mental stress in competitive life and incompatible diet, people are suffering from many lifestyle diseases. Amlapitta is one of them. It has adverse effect on the digestion and metabolism, with presence of symptoms like Avipaka, Klama, Utklesha, Amlodgara, Gauravta, Hrit Kantha Daha and Aruchi. Ayurveda is a holistic science which provides solutions with the help of natural resources as a principle of management. Different Ayurvedic literatures were scrutinized for description of Aahar (Diet)- Vihar (lifestyle) and drug Gudadi modaka has been taken from Chakradutta Amlapitta chikitsa for the management of Amlapitta. The 30 patient were selected for the study between the age group of 20–70 years from the OPD of Rajiv Gandhi Government Post Graduate Ayurvedic College and Hospital, Paprola, H.P. Patients were selected on the basis of specially prepared assessment criteria. Patients of both groups showed good improvement in the symptoms of Amlapitta. Patients of group II (Gudadi modak + Aahar -Vihara) showed slightly more significant results. Gudadi modak & proper dietary routine discipline has important role to achieve early and better result. To follow the code of Pathya & Apatyha and drug intake is the basic management of this disease. It is devoid of any side effect.